High‐Efficiency Carriers’ Separation Strategy Based Ultrasmall‐Bandgap CuWO4 Sono‐Enhances GSH Antagonism for Cuproptosis Cascade Immunotherapy - Lichao Zhu; Zhisheng Guo; Yu Luo; Haiyan Huang; Kexin Zhang; Bingbing Duan; Renmiao Peng; Haochen Yao; Chao Liang; Kaiyang Wang (Advanced Science)
Abstract The spatiotemporal sequential treatment strategy of promoting rapid separation of charge carriers, amplifying oxidative stress, increasing the low content of intracellular Cu, enhancing cuproptosis, and cascading activation of immunotherapy is considered one of the most effective techniques for improving the comprehensive therapy of tumors. Herein, copper tungstate (CuWO₄, CWO) nanoparticles with ultrasmall bandgap (1.71 eV) is developed as both piezoelectric‐catalysis agents and copper nanocarriers for synergistic sono‐enhanced cuproptosis. Owing to the unique bandgap microstructure, exposure to ultrasound (US) significantly increase the generation of reactive oxygen species (ROS) and the release of Cu2+ from CWO. Additionally, ≈60% of glutathione (GSH) and nicotinamide adenine dinucleotide phosphate (NADPH) are consumed in situ, leading to oxidative stress, ferroptosis, and cuproptosis in cancer cells. This cascading approach induces substantial mitochondrial dysfunction and the release of damage‐associated molecular patterns (DAMPs), which promotes immunogenic cell death (ICD) and augments antitumor immunity. Both in vitro and in vivo studies have shown that this sono‐enhanced cuproptosis‐based therapy could effectively suppress tumor growth. Overall, this study investigates a novel Structure‐Function therapeutic approach that combines piezoelectric catalysis, ferroptosis, cuproptosis, and cascade activation of immune regulation, opening up new possibilities for addressing the challenges associated with conventional cuproptosis therapy.